2018
DOI: 10.1016/j.enbuild.2018.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Why method matters: Temporal, spatial and physical variations in LCA and their impact on choice of structural system

Abstract: Life Cycle Assessment (LCA) is increasingly used as an early-stage design-decision tool to support choices of structural system. However LCA modellers must first make numerous methodological decisions, and the resultant wide variations in approach are often inadequately described by the modellers. This paper identifies, and quantifies, the three major areas of methodological variation. These are: temporal differences in the stages considered; spatial differences in the material boundaries; and physical dispari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 24 publications
0
43
0
2
Order By: Relevance
“…Impacts vary between 50-87 kg CO2-eq/m2 corresponding to between 5-22% of the whole life embodied impacts of the buildings, which is somewhat lower than for other life cycle stages. However as Moncaster et al (2018) point out the figures are frequently based on limited evidence. The effect of adding demolition activities and transport to suitable processing sites (stages C1-2) would also increase the figures and percentages for the end of life stage.…”
Section: End-of-life (Modules C3-c4)mentioning
confidence: 99%
“…Impacts vary between 50-87 kg CO2-eq/m2 corresponding to between 5-22% of the whole life embodied impacts of the buildings, which is somewhat lower than for other life cycle stages. However as Moncaster et al (2018) point out the figures are frequently based on limited evidence. The effect of adding demolition activities and transport to suitable processing sites (stages C1-2) would also increase the figures and percentages for the end of life stage.…”
Section: End-of-life (Modules C3-c4)mentioning
confidence: 99%
“…One of the key challenges for calculating embodied impacts from buildings is the choice of carbon coefficient for materials at the early design stage before they have been fully specified (Moncaster et al 2018). For concrete, the potential variations are almost infinite, dependent on the type and proportions of cement and aggregates, the addition of admixtures and plasticisers, and on the specific manufacturers' plants, processes and fuels.…”
Section: Previous Research On the Embodied Carbon Of Cement And Concretementioning
confidence: 99%
“…A review by Pomponi and Moncaster (2018) found that this variation has led to a wide range of energy and carbon coefficients being assumed by academic researchers, in developing case studies of buildings. It has also led to considerable uncertainty for designers as to which is the appropriate value to use for the embodied carbon of concrete at the early design stage of a building, and the potential for extremely differing answers, as demonstrated by Moncaster et al (2018).…”
Section: Previous Research On the Embodied Carbon Of Cement And Concretementioning
confidence: 99%
“…A curiosity associated with one of these [20] is that when extending the assessment to include biogenic carbon according to the Cherubini method [21], the carbon cost associated with the use of biomass energy outweighed the carbon benefit associated with storage, and the relative advantage of timber was actually reduced. Although concrete has lower EC than timber per unit of mass [13], there is much evidence to suggest that the use of timber results in buildings with lower EC [22].…”
Section: Lcas Of Buildings Using Timber Structuresmentioning
confidence: 99%